The efficacy of health surveys and polymerase chain reaction tests prior to judo tournaments during the COVID-19 pandemic - Sakuyama, N.; Mikami, Y.; Ikumi, A.; Fujita, N.; Nagahiro, S. (Cureus, 2022)
Background: As of October 2021, sports activities require preventive measures against coronavirus disease 2019 (COVID-19) infection. Judo, a close-contact sport, demands careful prevention with great consideration to the risk of infection. The All Japan Judo Federation Medical Science Committee (AJJF) designed COVID-19 prevention protocols from a medical perspective and developed policies for safe regular practices and tournaments. Objective and Methods: We aim to examine the efficacy of health surveys and polymerase chain reaction (PCR) tests prior to judo tournaments, as mandated by the tournament policy. Infection prevention managers were installed prior to tournaments. Two weeks prior to each tournament, these managers drafted health inventory forms for athletes and related parties to check for COVID-19-associated symptoms. Although PCR testing prior to tournaments was not required by policy, the AJJF conducted them (directly and by mail) prior to six tournaments from October 2020 to September 2021 for athletes whose health inventory forms listed no symptoms. Results: One of the athletes was not tested and was unable to participate in a tournament due to the symptoms indicated in their health inventory form. Testing began in October 2020 and was conducted until September 2021 for 2,073 athletes over the duration of six tournaments. The SARS-CoV-2 virus was detected in 11 (0.29%) athletes. In tournaments held until April 2021, SARS-CoV-2 was detected in only one of the 1,173 (0.08%) athletes tested. However, prior to tournaments held from July 2021 onward, when variants became prevalent, SARS-CoV-2 was detected in 10 (1.1%) of the 900 athletes tested (p < 0.05). No clusters were reported in association with any tournament. Conclusion: We believe that drafting health inventory forms two weeks prior to judo tournaments was essential and kept the participants alert. However, as variants emerged, some participants who were positive could not be detected through their inventory forms; this demonstrates the need for caution when relying on health inventory forms alone.